2013 IEEE 39th Photovoltaic Specialists Conference (PVSC) 2013
DOI: 10.1109/pvsc.2013.6744976
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of nitride-on-phosphide hybrid tandem solar cells by using surface-activated bonding

Abstract: Group-III nitride-on-phosphide hybrid tandem solar cells were fabricated using surface-activated bonding. The bottom surface of nitride top cells grown on GaN substrates was bonded on the top surface of InGaP-based bottom cells grown on n-GaAs substrates. Their tandem-cell operation was successfully demonstrated by confirming that the open-circuit voltage (VOC) of tandem cells was enhanced. It was also found that the electrical properties of the bonding interface do not induce fatal effects on the performance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…27) We successfully bonded the backsides of nitride-based cells fabricated on GaN substrates were successfully bonded to epitaxially grown InGaP cell structures by SAB so that nitride/InGaP-double-junction cells were formed. 28) We also measured the I-V characteristics of p-n junctions fabricated from a variety of semiconductor layers with different doping concentrations. 29) We found that the resistance across the bonding interface R interface decreased as the concentrations of impurities in p-and n-doped layers increased.…”
Section: Introductionmentioning
confidence: 99%
“…27) We successfully bonded the backsides of nitride-based cells fabricated on GaN substrates were successfully bonded to epitaxially grown InGaP cell structures by SAB so that nitride/InGaP-double-junction cells were formed. 28) We also measured the I-V characteristics of p-n junctions fabricated from a variety of semiconductor layers with different doping concentrations. 29) We found that the resistance across the bonding interface R interface decreased as the concentrations of impurities in p-and n-doped layers increased.…”
Section: Introductionmentioning
confidence: 99%
“…A multijunction GaInN-based solar cell was previously fabricated by the mechanical stack method. 22) On the other hand, there is no report of a multijunction nitride-based solar cell using a tunnel junction fabricated by crystal growth.…”
mentioning
confidence: 99%